Photocatalyst suitable for polyethylene upgrading recycling production of ethylene and propionic acid and preparation and application thereof
Patent Information
- Application Number
- CN202611133779.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-11-03
AI Technical Summary
Existing technologies for the conversion of polyethylene waste are subject to harsh conditions and low efficiency. TiO2 photocatalysts have high photogenerated carrier recombination rates and low quantum efficiency, making it difficult to efficiently convert them into ethylene and propionic acid.
Oxygen vacancy defects were introduced into TiO2 and loaded with CuPd bimetal. CuPd was uniformly loaded on the TiO2 surface by ice crystal photodeposition to construct a synergistic catalytic system of oxygen vacancy and CuPd bimetal, which broadened the photoresponse range, suppressed electron-hole pair recombination, and promoted the migration of photogenerated carriers.
The efficient photocatalytic decarboxylation of succinic acid, a product of polyethylene digestion, was achieved to produce ethylene and propionic acid. This method exhibits high selectivity and low energy consumption, significantly improving catalytic activity and stability.
Smart Images

Figure CN123024554A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of waste plastic resource utilization technology, specifically to a CuPd bimetallic TiO2 photocatalyst containing oxygen vacancies, its preparation method, and its application in the photocatalytic conversion of polyethylene waste into ethylene. Background Technology
[0002] Polyethylene (PE) is one of the most widely produced and used general-purpose plastics, characterized by its light weight, durability, and excellent chemical stability. It is widely used in packaging materials, agricultural films, pipes, and containers. However, PE is extremely inert; its molecular chain consists only of C-C and CH bonds, containing no double bonds or aromatic structures, making it virtually impossible to degrade under natural conditions. Traditional landfill and incineration methods not only consume land resources but also generate secondary pollution. Therefore, developing efficient and clean technologies for the resource utilization of polyethylene waste has significant environmental and economic value.
[0003] Chemical recycling technologies for polyethylene mainly include pyrolysis and catalytic cracking, but these typically require high temperatures (400-700℃), resulting in high energy consumption and poor product selectivity, primarily producing a wide distribution of liquid oils, waxes, and gaseous hydrocarbons. In recent years, photocatalysis, utilizing solar energy to drive chemical reactions, has significant advantages such as mild reaction conditions and environmental friendliness, showing broad application prospects in the field of waste plastic recycling. TiO2, as one of the most widely studied photocatalysts, possesses advantages such as high photocatalytic activity, stable structure, low cost, and low toxicity. However, its band gap is relatively wide (approximately 3.2 eV), meaning it can only be excited by ultraviolet light, and its photogenerated carrier recombination rate is high, resulting in relatively low quantum efficiency.
[0004] To enhance the photocatalytic performance of TiO2, researchers have developed various modification strategies. Among these, oxygen vacancy defect engineering can introduce defect energy levels into the TiO2 bandgap, broadening the photoresponse range to the visible light region. Simultaneously, it acts as a trapping center for photogenerated electrons, effectively suppressing electron-hole pair recombination. Metal loading (such as Pt, Pd, Au, and Cu) can construct active sites on the TiO2 surface, promoting the separation and migration of photogenerated charges. In recent years, bimetallic synergistic modification strategies have attracted widespread attention due to their ability to simultaneously regulate charge separation efficiency and surface reaction pathways. For example, PdCu alloy-modified TiO2 exhibits excellent performance in both the photocatalytic oxidation of PET and the Stille coupling reaction.
[0005] Significant progress has been made in the field of photocatalytic conversion of polyethylene. In 2023, Professor Qiao Shizhang's team at the University of Adelaide reported an atomic engineering strategy in *Science Advances* to modify TiO2 photocatalysts with atomically dispersed Pd species (Pd1-TiO2) to selectively convert PE to ethylene and propionic acid via a dicarboxylic acid intermediate under mild conditions. This catalyst exhibited an ethylene production rate of 531.2 μmol / g / h, 408 times that of the original TiO2, and a selectivity of up to 98.8% for the liquid-phase product propionic acid. Furthermore, studies have also prepared Ni cluster-modified oxygen-vacancy-rich TiO2 nanosheets via plasma treatment for the photocatalytic degradation of low-density polyethylene.
[0006] Currently, there are few reports on combining oxygen vacancy defect engineering with CuPd bimetallic support for the photocatalytic conversion of polyethylene waste into ethylene. Therefore, this invention provides an oxygen-vacancy-containing TiO2 photocatalyst supported on CuPd bimetal, its preparation method, and its application. Summary of the Invention
[0007] To address the aforementioned technical problems and shortcomings in this field, this invention provides a CuPd bimetallic oxygen-vacancy-containing TiO2 photocatalyst, its preparation method, and its applications, which can solve the problems of harsh conversion conditions and low efficiency in existing polyethylene technologies. This invention uses oxygen-vacancy-containing TiO2 as a substrate photocatalyst to photocatalyze the conversion of succinic acid, a product of PE digestion. Pd serves as the active site for succinic acid adsorption and decarboxylation, while Cu promotes the desorption of ethylene, achieving highly efficient photocatalytic conversion of succinic acid to ethylene and propionic acid.
[0008] The specific technical solution is as follows: In a first aspect, the present invention provides a photocatalyst suitable for the upgrading and recycling of polyethylene to produce ethylene and propionic acid, comprising oxygen-vacancy TiO2 and CuPd bimetal supported on the surface of oxygen-vacancy TiO2. In the CuPd bimetallic compound, the mass ratio of Cu to Pd is (0.1~0.8):1, for example, 0.19:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.39:1, 0.4:1, 0.45:1, 0.5:1, etc., preferably (0.25~0.5):1. Under these preferred conditions, the photocatalyst exhibits better ethylene and propylene generation rates, as well as the total ethylene and ethane generation rate, when used for photocatalytic decarboxylation of succinic acid.
[0009] In some preferred embodiments, the oxygen vacancies are introduced by reducing TiO2. Specifically, this involves mixing TiO2 (powder) with NaBH4 (powder) and then heat-treating the mixture under an inert atmosphere to obtain an oxygen-vacancy-containing TiO2 support (which can be denoted as O).v -TiO2). Furthermore, the preferred mass ratio of TiO2 to NaBH4 is 1:(0.5~2), and even more preferably 1:1. Under these preferred conditions, the photocatalyst exhibits better ethylene, ethane, and propylene production rates when used for photocatalytic decarboxylation of succinic acid.
[0010] The inert atmosphere described in this invention refers to a gaseous atmosphere that does not participate in the reaction, such as an argon atmosphere and / or a nitrogen atmosphere.
[0011] In some preferred embodiments, the heat treatment is performed at a temperature of 300-320°C for 1-2 hours.
[0012] In some preferred embodiments, TiO2 is P25.
[0013] In some preferred embodiments, based on the mass of oxygen-containing TiO2, the Pd loading is 0.5wt% to 2wt% (e.g., 1wt%, 1.1wt%, etc.) and the Cu loading is 0.2wt% to 0.8wt% (e.g., 0.4wt%). Under these preferred conditions, the photocatalyst exhibits superior ethylene, ethane, and propylene production rates when used for photocatalytic decarboxylation of succinic acid.
[0014] Secondly, the present invention provides a preferred preparation method for the photocatalyst described in the first aspect, which uses ice crystal photodeposition to load CuPd bimetal onto the surface of oxygen-vacant TiO2, specifically including the following steps: S1, oxygen-vacancy-containing TiO2, palladium precursor and copper precursor are mixed in deionized water under an inert atmosphere and then frozen; S2, the frozen sample undergoes photodeposition reaction under light conditions; S3. The sample after photodeposition reaction is washed and dried to obtain the photocatalyst.
[0015] Using the above-mentioned preferred preparation method, the resulting photocatalyst exhibits superior ethylene, ethane, and propylene production rates when used for photocatalytic decarboxylation of succinic acid.
[0016] In some preferred embodiments, in step S1, the palladium precursor includes at least one of tetraaminopalladium nitrate and sodium tetrachloropalladium.
[0017] In some preferred embodiments, in step S1, the copper precursor includes at least one of copper nitrate and copper chloride.
[0018] In some preferred embodiments, the illumination conditions in step S2 include: 300~500W xenon lamp irradiation for 2~10 minutes (e.g., 5 minutes).
[0019] Thirdly, the present invention provides a method for photocatalytic decarboxylation of succinic acid to obtain ethylene and propionic acid, comprising: irradiating a mixture containing the photocatalyst described in the first aspect and succinic acid under an inert atmosphere to carry out a photocatalytic reaction.
[0020] This invention's photocatalyst introduces oxygen vacancy defects into TiO2 and further loads CuPd bimetallic sites, achieving a synergistic effect between oxygen vacancies and bimetallic sites, significantly improving the photocatalytic decarboxylation conversion efficiency. Under conditions of 365nm ultraviolet irradiation, pH=1~7, temperature 30~70℃, and reaction time 1~8h, this photocatalyst can achieve highly efficient photocatalytic decarboxylation of succinic acid, a polyethylene digestion product, to prepare ethylene. It exhibits high catalytic activity and excellent stability, while simultaneously achieving low-energy consumption and high selectivity in converting polyethylene derivatives into high-value chemicals such as ethylene.
[0021] In some preferred embodiments, the photocatalytic reaction conditions include: a light wavelength of 365 nm, a reaction temperature of 30-70 °C, a mixed solution pH of 1-7, preferably 3-5, more preferably 4, and a reaction time of 0.5-8 h (e.g., 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, etc.).
[0022] Fourthly, the present invention provides the application of the photocatalyst described in the first aspect or the method described in the third aspect in the degradation of polyethylene to produce ethylene, ethane and propionic acid.
[0023] The photocatalyst of this invention exhibits good conversion efficiency for both succinic acid (a product of polyethylene digestion) and actual polyethylene digestion solutions under ultraviolet light.
[0024] In some preferred embodiments, the application specifically includes: Step 1: Construct a reaction system comprising polyethylene and an acid solvent, and carry out a digestion reaction under heating conditions to prepare succinic acid; Step 2: Photocatalytic reaction is carried out by irradiating a mixture containing the photocatalyst described in the first aspect and succinic acid under an inert atmosphere.
[0025] In some preferred embodiments, in step one, the acid solvent includes nitric acid.
[0026] In some preferred embodiments, in step one, the digestion reaction is carried out at a temperature of 160-180°C for 8-12 hours.
[0027] Pure-phase TiO2 (P25) suffers from a wide band gap (approximately 3.2 eV), can only be excited by ultraviolet light, exhibits rapid recombination of photogenerated electron-hole pairs, and has insufficient surface active sites, limiting further improvements in its photocatalytic efficiency. This invention introduces oxygen vacancy defects into TiO2 and loads CuPd bimetallic material as a photocatalyst. Oxygen vacancies introduce defect energy levels into the TiO2 band gap, effectively broadening the photoresponse range. Simultaneously, they act as trapping centers for photogenerated electrons, significantly inhibiting electron-hole pair recombination. Pd is a key active center for succinic acid adsorption and decarboxylation, effectively promoting the breaking of C / C bonds. The presence of Cu weakens the strong adsorption of ethylene by Pd, promoting ethylene desorption and inhibiting its excessive hydrogenation. More importantly, there is a synergistic effect between oxygen vacancies and the CuPd bimetallic material: the localized electronic structure introduced by oxygen vacancies facilitates the anchoring and dispersion of metal sites, promoting the migration of photogenerated carriers to metal sites and reducing photogenerated carrier recombination. The combined effect of vacancies and metal loading significantly enhances the photocatalytic activity and ethylene selectivity of the catalyst.
[0028] Compared with the prior art, the beneficial effects of this invention are as follows: 1) This invention introduces oxygen vacancy defects into TiO2 to form defect energy levels in the band gap, effectively broadening the photoresponse range of the catalyst to the visible light region; at the same time, oxygen vacancies can serve as trapping centers for photogenerated electrons, significantly suppressing the recombination of photogenerated electron-hole pairs and improving quantum efficiency.
[0029] 2) This invention introduces oxygen vacancies through NaBH4 solid-phase reduction, which is a simple and controllable process that avoids the use of strong reducing agents and can effectively maintain the anatase crystal structure of TiO2.
[0030] 3) This invention utilizes ice crystal photodeposition method on O v - TiO2 surface is loaded with uniformly dispersed Pd and Cu metals. Ice crystal photodeposition method uses ice crystals to confine metal ions on the surface of photocatalyst, which can achieve uniform loading of metal species at low temperature and avoid metal particle agglomeration.
[0031] 4) This invention effectively suppresses the hydrogenation of gaseous product ethylene to ethane, and has higher selectivity for the high-value product ethylene. At the same time, it produces highly selective liquid product propionic acid, which has significant economic benefits. Attached Figure Description
[0032] Figure 1 The graph shows the gas phase product yields at different times for the photocatalysis of succinic acid by the catalyst of Example 1 under the conditions of Example 13.
[0033] Figure 2 The graph shows the liquid phase product yield at different times for the photocatalysis of succinic acid by the catalyst of Example 1 under the conditions of Example 13. Detailed Implementation
[0034] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Operating methods not specifically described in the following embodiments are generally performed under conventional conditions or as recommended by the manufacturer. Contents not described in detail in this specification are prior art known to those skilled in the art. Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0035] Example 1: Step (1): Take 1.0 g of P25 powder and 1 g of NaBH4 powder, and grind them thoroughly in an agate mortar until homogeneous. Transfer the mixture to a porcelain boat and place it in a tube furnace. Purge with high-purity Ar gas (flow rate 100 mL / min) for 30 min to purge the air, and heat to 300 °C at a rate of 5 °C / min, holding for 1 hour. After the reaction is complete, allow it to cool naturally to room temperature. Wash the obtained product three times with deionized water, then twice with anhydrous ethanol, and dry under vacuum at 80 °C for 12 h to obtain the modified P25 material rich in oxygen vacancies, denoted as O. v -P25.
[0036] Step (2): Take 100mg O v -P25 was dispersed in 15 mL of deionized water, and 0.4 mL of copper nitrate trihydrate solution (Cu content 1 mg / mL) and 0.202 mL of tetraaminopalladium nitrate solution (Pd content 5 mg / mL) were added. After stirring in an Ar atmosphere for 30 min, the mixture was placed in a refrigerator and frozen overnight.
[0037] Step (3): Irradiate the frozen sample under a 300W xenon lamp for 5 minutes to carry out photodeposition reaction.
[0038] Step (4): After the frozen liquid thaws at room temperature, it is filtered and washed three times with deionized water, and then dried overnight in a vacuum drying oven at 40°C to obtain a CuPd bimetallic P25 photocatalyst containing oxygen vacancies, denoted as Cu. 0.4 Pd1-O v -P25.
[0039] Example 2: The only difference from Example 1 is that the amount of NaBH4 powder used is changed to 0.5g; all other aspects are the same, resulting in the photocatalyst Cu. 0.4 Pd1-O v -P25 (1:0.5).
[0040] Example 3: The only difference from Example 1 is that the amount of NaBH4 powder used is changed to 2g; all other aspects are the same, resulting in the photocatalyst Cu. 0.4 Pd1-O v -P25 (1:0.5).
[0041] Example 4: The only difference from Example 1 is that the tetraaminopalladium nitrate solution was not used; all other aspects were the same, resulting in the photocatalyst Cu. 0.4 -O v -P25.
[0042] Example 5: The only difference from Example 1 is that copper nitrate trihydrate solution was not used; all other aspects were the same, resulting in the photocatalyst Pd1-O. v -P25.
[0043] Example 6: The only difference from Example 1 is that the amount of copper nitrate trihydrate solution used is changed to 0.2 mL; all other aspects are the same, resulting in the photocatalyst Cu. 0.2 Pd1-O v -P25.
[0044] Example 7: The only difference from Example 1 is that the amount of copper nitrate trihydrate solution used is changed to 0.8 mL; all other aspects are the same, resulting in the photocatalyst Cu. 0.8 Pd1-O v -P25.
[0045] Comparative Example 1: The only difference from Example 1 is the absence of step (1), and the replacement of O with an equal mass of P25 in step (2). v -P25, all others are the same, yielding the photocatalyst Cu. 0.4 Pd1-P25.
[0046] Comparative Example 2: O prepared in Example 1 v -P25, as the comparative example 2 sample, was not subjected to metal loading treatment.
[0047] Comparative Example 3: P25 powder was used as the sample for Comparative Example 3 to serve as a blank control.
[0048] Example 8: PE nitric acid digestion produces succinic acid: Before the formal catalytic experiment began, the ability to produce succinic acid by hydrothermal digestion of PE with nitric acid was verified. Details are as follows: The digestion experiment was carried out in a 200 mL hydrothermal reactor. Several grams of PE powder were placed in a high-pressure reactor with a polytetrafluoroethylene liner and pretreated at 160 °C for 8 h. The resulting PE decomposition solution was analyzed, and the results are shown in Table 1. The results show that in the low to medium PE concentration range (2~4 mg / mL), the succinic acid yield increased approximately linearly with the increase of PE concentration, and the amount of by-products (acetic acid, glutaric acid, adipic acid) was always at a very low level. This indicates that in this concentration range, the oxidizing power of nitric acid is sufficient, and the chain breaking and oxidation process of PE mainly produces succinic acid, and the side reactions are effectively suppressed.
[0049] Table 1. Distribution of products after decomposition at different PE concentrations Example 9: Photocatalytic conversion of succinic acid: The catalysts prepared in Example 1 and Comparative Examples 1-3 were used to photocatalytically convert succinic acid to investigate the effects of vacancies and metal support on catalyst activity, as detailed below: The activity experiment was conducted in a 150 mL reactor equipped with an outer cooling water circulation system. The reaction light source was a 365 nm ultraviolet lamp. 10 mg of catalyst and 10 mL of 10 mg / mL succinic acid solution were added to the reactor. The pH of the reaction was adjusted to 4 using 0.1 mol / L NaOH solution. The apparatus was then sealed with a transparent quartz glass lid, and stirring and water circulation were started. The magnetic stirrer speed was set to 300 rpm. -1 The temperature of the cooling circulating water was adjusted to the required experimental temperature. Ar gas was introduced into the reactor through the inlet valve and continued for 30 minutes. The inlet and outlet valves were then closed to ensure complete replacement of the gas in the reactor with the reactant gas. The light source above the reactor was then turned on to begin the photocatalytic reaction, with a reaction time set to 3 hours. After the reaction, the reactor was allowed to cool to room temperature. 1 mL of gas was extracted from the reactor using a 1 mL gas injection needle, and the concentrations of C2H4 and C2H6 were measured by gas chromatography. The reaction apparatus was then opened, and the catalyst and liquid were removed. 1 mL of the liquid was taken using a 2 mL syringe with a filter, and the concentrations of the liquid products, propionic acid and adipic acid, were measured by liquid chromatography. The results are shown in Table 2.
[0050] Table 2. Performance comparison of different catalysts in the photocatalytic conversion of succinic acid to C2 hydrocarbons and propionic acid In terms of overall activity, the catalyst performance exhibits a clear gradient: Example 1 (oxygen vacancy + CuPd) > Comparative Example 1 (CuPd only) > Comparative Example 2 (oxygen vacancy only) ≈ Comparative Example 3 (original P25). Specifically, the ethylene, ethane, and propionic acid formation rates of Example 1 are as high as 888.97 μmol / g / h (where g represents catalyst mass), 400.66 μmol / g / h (where g represents catalyst mass), and 418.36 μmol / h, respectively, which are far superior to the other control groups.
[0051] This significant increase in activity can be attributed to a highly efficient synergistic catalytic mechanism between oxygen vacancies and metal support, the specific reasons for which are analyzed below: (1) Oxygen vacancy (O v The substrate activation and anchoring effect: Comparative Example 2 (O only) v Compared with Comparative Example 3 (original P25), it can be seen that the yields of ethylene and ethane increased from 16.53 and 15.82 to 51.35 and 44.55 μmol / g / h, respectively, after introducing oxygen vacancies alone, indicating that oxygen vacancies themselves have certain intrinsic activity. This is mainly because oxygen vacancies, as Lewis acid sites, can effectively adsorb and activate the carboxyl group (-COOH) in succinic acid molecules, lowering the activation energy barrier of the reaction. At the same time, oxygen vacancies provide abundant anchoring sites for subsequent metal loading, promoting metal dispersion and stability.
[0052] (2) The catalytic active center role of CuPd bimetals: Comparing Comparative Example 1 (CuPd only) with Comparative Example 3 (original P25), it can be seen that when only CuPd is loaded without introducing oxygen vacancies, the ethylene yield (540.05 μmol / g / h) is significantly improved, indicating that Pd is the core active site for activating C-C bonds to undergo decarboxylation and generate C2 hydrocarbons. However, the activity of Comparative Example 1 is still much lower than that of Example 1. This is attributed to the limited dispersion and electron density of the metal particles in the absence of oxygen vacancies, which prevents the catalytic efficiency from being maximized.
[0053] (3) Geometric-electronic dual synergistic effect of oxygen vacancies and CuPd bimetals.
[0054] Comparative Example 1 (O) V As can be seen from the comparison with CuPd and Comparative Example 1 (CuPd only), the yields of ethylene, ethane, and propionic acid were significantly increased after the introduction of oxygen vacancies. This significant difference indicates a synergistic effect between the two: the abundant oxygen vacancies on the P25 surface enhance the metal-support interaction, resulting in more uniform anchoring and dispersion of Cu and Pd metal sites, exposing more unsaturated coordination active sites, promoting the migration of photogenerated carriers to metal sites, and reducing the recombination of photogenerated carriers.
[0055] Example 10: The catalysts prepared in Examples 1 and 2-3 were used to photocatalytically convert succinic acid in order to explore the optimal ratio of P25 to NaBH4. The specific operation was the same as in Example 9, and the results are shown in Table 3.
[0056] Table 3 Comparison of the performance of P25 and NaBH4 ratios on the photocatalytic conversion of succinic acid to C2 hydrocarbons and propionic acid. The results show that the mass ratio of P25 to NaBH4 has a significant impact on the photocatalytic conversion performance of succinic acid by the final catalyst. When the P25:NaBH4 ratio is 1:1, the formation rates of ethylene, ethane, and propionic acid all reach their optimal values. In contrast, when the amount of NaBH4 is halved (ratio 1:0.5) or doubled (ratio 1:2), the yields of the three products decrease to varying degrees. This indicates that moderate NaBH4 reduction treatment can effectively construct the optimal concentration of oxygen vacancies, while insufficient or excessive amounts of reducing agent are detrimental to the improvement of catalytic performance.
[0057] The specific reasons are analyzed as follows: Insufficient NaBH4 dosage (Example 2, 1:0.5) resulted in inadequate oxygen vacancy generation. When the NaBH4 dosage was halved, the number of active hydrogen species generated in the reaction system was limited, only partially reducing the Ti on the P25 surface. 4+ The resulting oxygen vacancy concentration is low. The lack of oxygen vacancies limits its adsorption and activation ability for succinic acid molecules, and also reduces the anchoring sites of CuPd bimetal, leading to poor metal dispersibility, increased particle size, and a decrease in the number of effective active sites, ultimately resulting in a significant decrease in catalytic activity.
[0058] Excessive NaBH4 dosage (Example 3, 1:2) led to overreduction and negative effects. This may be because excessive active hydrogen species could overreduce the P25 surface, forming too many oxygen vacancies and Ti. 3+ Defects. Studies have shown that a higher oxygen vacancy concentration is not necessarily better. Excessive lattice defects can disrupt the periodic crystal structure of TiO2, forming a large number of bulk recombination centers, which in turn accelerates the recombination of photogenerated electrons and holes and reduces photonic quantum efficiency.
[0059] Example 11: The catalysts prepared in Examples 1 and 4-5 were used to photocatalytically convert succinic acid in order to investigate the effects of Cu and Pd metals on catalytic activity. The specific operation was the same as in Example 9, and the results are shown in Table 4.
[0060] Table 4. Performance comparison of metal support for the photocatalytic conversion of succinic acid to C2 hydrocarbons and propionic acid. The results show that the type of metal loading has a significant impact on the photocatalytic conversion performance of succinic acid. When only Cu is loaded (Example 4), the formation rates of ethylene, ethane, and propionic acid are all extremely low, indicating that Cu species alone is difficult to effectively catalyze the C-C bond breaking reaction of succinic acid. However, the ethylene selectivity is relatively high (ethylene / C2 hydrocarbon ratio can reach 76%). When only Pd is loaded (Example 5), the overall activity is significantly improved, but the selectivity is poor when used alone, and the product is dominated by the deeply hydrogenated product ethane. When Cu and Pd are co-loaded, the introduction of Cu not only further improves the overall catalytic activity, but more importantly, it regulates the selectivity of the reaction pathway, causing the decarboxylation product to shift from the over-hydrogenated ethane to the high-value ethylene.
[0061] The specific reasons are analyzed as follows: In the photocatalytic C / C bond breaking reaction of organic acids such as succinic acid, Cu-based catalysts have very limited catalytic activity at a single Cu site. They also have weak adsorption energy for reaction intermediates, making it difficult to effectively stabilize carbocations or acyl intermediates generated during decarboxylation. At the same time, the supply capacity of active hydrogen species on the Cu surface is insufficient, resulting in both decarboxylation and hydrogenation reactions being unable to proceed efficiently.
[0062] Pd is a classic active metal for hydrogenation and decarboxylation. Its surface can effectively adsorb and activate succinic acid molecules and promote the breaking of C-C bonds to generate ethylene intermediates. However, Pd's strong hydrogen spillover and hydrogen activation capabilities make it difficult for the generated ethylene to desorb from the Pd surface. Instead, it is further hydrogenated to generate ethane, resulting in ethane becoming the main product and ethylene having extremely low selectivity.
[0063] The Cu+Pd bimetallic loading weakens the adsorption energy and hydrogenation probability of ethylene on the catalyst surface, enabling ethylene to desorb into the gas phase in a timely manner.
[0064] Example 12: The catalysts prepared in Examples 1 and 6-7 were used to photocatalytically convert succinic acid in order to investigate the effect of different Cu and Pd metal ratios on catalytic activity. The specific operation was the same as in Example 9, and the results are shown in Table 5.
[0065] Table 5 Comparison of the performance of Cu and Pd ratios on the photocatalytic conversion of succinic acid to C2 hydrocarbons and propionic acid. The results show that the Cu:Pd ratio of 0.4:1 exhibits the best performance in terms of total hydrocarbon yield, product distribution balance, and catalytic stability, making it the optimal metal ratio for the photocatalytic conversion of succinic acid.
[0066] The specific reasons are analyzed as follows: A low Cu ratio means insufficient geometric isolation of Pd sites, allowing ethylene to still be easily hydrogenated to ethane (ethylene / C2 hydrocarbon ratio of 51%). Insufficient Cu content limits the number of Cu-Pd cooperative interfaces, preventing the optimal total active site density for the decarboxylation reaction and resulting in a lower total hydrocarbon yield. Excess Cu, on the other hand, dilutes the Pd decarboxylation active centers, reducing the number of Pd-Pd active pairs and inhibiting the rate of the main decarboxylation reaction.
[0067] Example 13: The catalyst prepared in Example 1 was subjected to photocatalytic conversion of succinic acid to investigate the effect of different reaction times on the photocatalytic conversion of succinic acid. The specific operation was the same as in Example 9, with reaction times set to 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, and 8 h, respectively. The results are as follows: Figure 1 and 2 As shown.
[0068] The results show that with the extension of reaction time, the yields of ethylene and ethane in the gaseous products both show a continuous and stable increasing trend, and the ethylene selectivity remains at a high level of 60%~70%, indicating that the catalyst maintains excellent catalytic activity and stability during long-term reactions. Meanwhile, propionic acid, the core product of succinic acid decarboxylation, shows an approximately linear increase in its accumulation with reaction time.
[0069] Example 14: The catalyst prepared in Example 1 was subjected to photocatalytic conversion of actual PE decomposition liquid to investigate the application of the catalyst to actual PE decomposition liquid, as detailed below: The activity experiment was conducted in a 150 mL reactor equipped with an outer cooling water circulation system. The reaction light source was a 365 nm ultraviolet lamp. 10 mg of catalyst and 10 mL of 4 mg / mL PE decomposition solution (obtained as described in Example 8, with the pH adjusted to 4 using 0.1 mol / L NaOH solution) were added to the reactor. The apparatus was sealed with a transparent quartz glass lid, and then stirring and water circulation were started. The magnetic stirrer speed was set to 300 rpm. -1 The temperature of the cooling circulating water was adjusted to the required experimental temperature. Ar gas was introduced into the reactor through the inlet valve and continued for 30 minutes. The inlet and outlet valves were then closed to ensure complete replacement of the gas in the reactor with the reactant gas. The light source above the reactor was then turned on to begin the photocatalytic reaction, with a reaction time set to 3 hours. After the reaction, the reactor was allowed to cool to room temperature. 1 mL of gas was extracted from the reactor using a 1 mL gas injection needle, and the concentrations of C2H4 and C2H6 were measured by gas chromatography. The reaction apparatus was then opened, and the catalyst and liquid were removed. 1 mL of the liquid was taken using a 2 mL syringe with a filter, and the concentrations of the liquid products, propionic acid and adipic acid, were measured by liquid chromatography. The results are shown in Table 6.
[0070] Table 6. Application of catalysts in actual PE decomposition solutions In summary, this invention provides an oxygen-vacancy-containing TiO2 photocatalyst supported on CuPd bimetal and its preparation method, applicable to the production of ethylene and propionic acid from succinic acid, a product of polyethylene digestion. This invention introduces oxygen vacancy defects into TiO2 (P25) via NaBH4 solid-phase chemical reduction and further supports CuPd bimetal via ice crystal photodeposition, constructing an oxygen vacancy + CuPd bimetallic synergistic catalytic system. Oxygen vacancies can introduce defect energy levels into the band gap of TiO2, broadening the photoresponse range, and simultaneously act as trapping centers for photogenerated electrons, suppressing electron-hole recombination. In the CuPd bimetal, Pd is the key active center for succinic acid adsorption and decarboxylation; the introduction of Cu weakens the strong adsorption of ethylene by Pd, promoting ethylene desorption and inhibiting excessive hydrogenation. This invention achieves a mild conversion from polyethylene waste to high-value chemicals (ethylene and propionic acid), providing a new technical path for the resource utilization of waste plastics, and has significant environmental protection and economic benefits.
[0071] Furthermore, it should be understood that after reading the above description of the present invention, those skilled in the art can make various alterations or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims.
Claims
1. A photocatalyst suitable for the upgrading and recycling of polyethylene to produce ethylene and propionic acid, characterized in that, Including oxygen-vacancy TiO2 and CuPd bimetal supported on the surface of oxygen-vacancy TiO2; In the CuPd bimetallic compound, the mass ratio of Cu to Pd is (0.1~0.8):1, preferably (0.25~0.5):
1.
2. The photocatalyst according to claim 1, characterized in that, The oxygen vacancies are introduced by reducing TiO2. The specific operation includes: mixing TiO2 with NaBH4 and then heat-treating it under an inert atmosphere to obtain an oxygen-vacancy-containing TiO2 support. The mixing mass ratio of TiO2 to NaBH4 is 1:(0.5~2), preferably 1:1; The heat treatment is performed at a temperature of 300-320°C for 1-2 hours.
3. The photocatalyst according to claim 1, characterized in that, TiO2 is P25.
4. The photocatalyst according to claim 1, characterized in that, Based on the mass of oxygen-containing vacancy TiO2, the Pd loading is 0.5wt%~2wt% and the Cu loading is 0.2wt%~0.8wt%.
5. The method for preparing the photocatalyst according to any one of claims 1 to 4, characterized in that, The CuPd bimetal was loaded onto the oxygen-vacancy TiO2 surface using ice crystal photodeposition, specifically including the following steps: S1, oxygen-vacancy-containing TiO2, palladium precursor and copper precursor are mixed in deionized water under an inert atmosphere and then frozen; S2, the frozen sample undergoes photodeposition reaction under light conditions; S3. The sample after photodeposition reaction is washed and dried to obtain the photocatalyst.
6. The preparation method according to claim 5, characterized in that, In step S1: Palladium precursors include at least one of tetraaminopalladium nitrate and sodium tetrachloropalladium. Copper precursors include at least one of copper nitrate and copper chloride.
7. The preparation method according to claim 5, characterized in that, In step S2, the illumination conditions include: 300~500W xenon lamp illumination for 2~10 minutes.
8. A method for photocatalytic decarboxylation of succinic acid to obtain ethylene and propionic acid, characterized in that, include: The photocatalytic reaction is carried out under an inert atmosphere by irradiating a mixture containing the photocatalyst according to any one of claims 1 to 4 and succinic acid.
9. The method according to claim 8, characterized in that, The photocatalytic reaction conditions include: light wavelength 365nm, reaction temperature 30~70℃, pH of mixed solution 1~7 (preferably 3~5, more preferably 4), and reaction time 0.5~8h.
10. The use of the photocatalyst according to any one of claims 1 to 4 or the method according to claim 8 or 9 in the degradation of polyethylene to produce ethylene, ethane and propionic acid.
